Examination of the Biblical texts that form the basis of evangelical Christian support for Israel, with special reference to the response of the International Christian Embassy Jerusalem - Carstens, Jack E (Kaplan Centre for Jewish Studies, 2014)
Includes bibliographical references (leaves 113-116).